Substrate types and applications of MXene for surface-enhanced Raman spectroscopy - Liu, Zhi-Wei; Wang, Gong; Li, Yun-Fei; Yu, Yu (Frontiers in Chemistry, 2024)
Surface-enhanced Raman spectroscopy (SERS) has been widely used in the analysis of analytes because of its unique fingerprint characteristics, high sensitivity, and fast detection response. MXene is widely used in SERS studies among the various substrates due to its ultra-high chemical stability, excellent conductivity, hydrophilicity, and low fabrication cost. This mini-review summarizes MXene's research in the SERS field from two aspects. We reviewed MXene materials used as SERS substrates alone and combined with noble metal particles primarily. Subsequently, we outlined representative applications of MXene-based SERS in biomedicine, food safety, and environmental monitoring. Moreover, we discussed the technical bottleneck and the prospect of future development in this field.